Gaya Hidup Mahasiswa dalam Pengaruh Penggunaan Media Sosial - Ristiliana, Ristiliana; Salmiah, Salmiah; Farisa, Ghefira; Wati, Indah; Novita, Yulia (Universitas Batanghari Jambi, 2025)
The purpose of this study is to determine the level of lifestyle of students of the Economic Education study program in the influence of social media use. This research is a quantitative descriptive research, with the research subjects being students of Economics Education, while the object of the research is the lifestyle of students in the influence of social media use. The informants of this research were 3rd (three) semester economics education students. The data collection techniques used in this study were questionnaires and documentation. Data analysis techniques consist of data reduction, data presentation and drawing conclusions. Based on the results of research conducted on economic education students at UIN Suska Riau, the students' lifestyle in terms of the influence of social media use is categorized as high with a percentage of 68.8%. These results also show that through 3 (three) lifestyle indicators, namely activities, interests and opinions, the lifestyle of Economic Education students is considered positive because in general students agree with the positive sub-indicators and disagree with the negative sub-indicators. So the conclusion is that Economics Education students have a good lifestyle and are not exposed to negative things on the social media they use.